Wonder Woman. Volume 6, Bones - Azzarello, Brian (New 52., 2015)
Olympus must fall, and its rightful ruler must be restored. Wonder Woman is locked in a desperate battle with the First Born with the destiny of immortals at stake--and she must make a decision that will effect the lives of those she loves most.